Eat, Shop, Explore: The Ultimate Guide to Experiencing Taiwan's Night Markets - Zulianto, Mukhamad (Krisnadwipayana International Journal of Management Studies, 2024)
Taiwan's night markets are vibrant cultural hubs offering many experiences, ranging from culinary delights to unique shopping finds and immersive cultural encounters. This qualitative research aims to provide an in-depth exploration of Taiwan's night markets, focusing on the experiences of both locals and tourists. Through interviews, observations, and analysis, this paper uncovers the multifaceted aspects of Taiwan's night markets, highlighting their significance as socio-cultural spaces and tourism attractions. By delving into the sensory, social, and economic dimensions of night market experiences, this paper offers insights into the rich tapestry of Taiwanese street culture and its impact on local communities and the tourism industry.